Combination of Aspergillus niger culture and glycyrrhizic acid alleviates the toxic effects of multi-mycotoxins on broiler production performance and nutrient metabolism - Tu, Jinqiu; Li, Mengke; Wang, Ping; Wang, Lijun; Jin, Sanjun; Li, Xinxin; Chang, Juan; Yin, Qingqiang; Liu, Chaoqi; Zhu, Qun; Li, Maolong; Lu, Fushan (Frontiers in Nutrition, 2025)
IntroductionMycotoxins in animal diets cause a lot of economic loss in animal husbandry annually. The objective of this experiment was to evaluate the effect of combination of Aspergillus niger culture and glycyrrhizic acid (CANCGA) on alleviating multi-mycotoxin toxicity for broiler production performance and nutrient metabolism.MethodsA total of 500 one-day-old male broilers were randomly divided into 10 groups, 5 replications in each group and 10 broilers in each replication. The feeding period was 21 d. The dietary treatment included group A (the basal diet as the control group); group B (0.03 mg/kg aflatoxin B1 (AFB1) + 0.15 mg/kg zearalenone (ZEN) + 1.5 mg/kg deoxynivalenol (DON), low-dose mycotoxin diet); group C (0.07 mg/kg AFB1 + 0.5 mg/kg ZEN + 3.0 mg/kg DON, high-dose mycotoxin diet); groups D, E and F (basal diet supplemented with 0.2, 0.4 and 0.6 g/kg CANCGA, respectively); groups G, H and I (low-dose mycotoxin diet supplemented with 0.2, 0.4 and 0.6 g/kg CANCGA, respectively); group J (high-dose mycotoxin diet supplemented with 0.4 g/kg CANCGA).ResultsThe results demonstrated that broiler mortality in groups B and C was 2 and 6%, which in other groups was zero, indicating that CANCGA addition in diets could decrease broiler mortality caused by multi-mycotoxins. Average daily weight (ADG), metabolic rates of protein and phosphorus were significantly declined, while the ratio of daily feed intake and daily gain were significantly increased when dietary mycotoxin concentration was increased (p < 0.05). Compared with the control group, low-dose mycotoxin in diet could increase serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activity (p < 0.05), while decrease serum total protein (TP), albumin (ALB) and total cholesterol (TC) levels (p < 0.05). However, CANCGA addition could effectively reverse the above results. Compared with the low-dose mycotoxin group, the addition of 0.4 g/kg CANCGA could decrease serum ALT, AST, alkaline phosphatase (ALP), glucose (GLU), triglyceride (TG) and high-density lipoprotein (HDL) levels (p < 0.05), while increase ALB, TC levels and ALB/Globulin (GLB) (p < 0.05), indicating that CANCGA addition was able to reduce oxidative stress of broilers induced by multi-mycotoxins. The contents of residual AFB1, ZEN and DON in broiler excreta were significantly increased in the low-dose mycotoxin group (p < 0.05), compared to the control group; however, CANCGA addition could decrease AFB1, ZEA and DON contents in broiler excreta. Serum metabolomics showed that metabolites such as creatine, N-acetyl-L-phenylalanine and linoleic acid as well as metabolic pathways related to glycine, serine, threonine, cysteine, methionine, selenium compounds and linoleic acid metabolisms were regulated by CANCGA addition to alleviate nutrient metabolic disorders caused by multi-mycotoxins.DiscussionIn conclusion, CANCGA was found to be effective in alleviating multi-mycotoxin toxicity for broilers’ growth performance through reducing oxidative stress and positively regulating nutrient metabolisms.